Gaming and price spikes in electric power markets. - Xiaohong Guan (IEEE Transactions on power systems)
Many challenging issues arise under the newly deregulated competitive electric power markets. Instead of centralized decision-making in a vertically integrated environment as in the past, decision-making is now decentralized and driven by market forces. Gaming and price spikes have been observed in almost every electricity market but explicit analysis of these phenomena is rare. In this paper, the authors study historical bidding behavior to see how power suppliers and demand service providers were actually bidding in the California day-ahead energy market. Based on their observations, they formulate a Prisoner's dilemma matrix game and introduce the notion of ?opportunistic tacit collision? to explain strategic bidding behaviors in which suppliers withhold generation capacity from the market to drive up prices. This explanation is applicable with or without market power, transmission constraints, and insufficient supply, and is only enhanced by these factors. Their analysis is generally applicable to any uniform price electricity market in which there is significant insensitivity to price on the demand side